Social Support and Entrepreneurial Skills as Antecedents of Entrepreneurial Behaviour - Muhammad Shoaib, Farooq (Universiti Malaysia Sarawak (UNIMAS), 2016)
This thesis introduces and tests a new theoretical framework to investigate the significance of social support and entrepreneurial skills for determining entrepreneurial behaviour of individuals. Theory of planned behaviour, which has remained often braced in the pitch of entrepreneurship literature, is employed as underpinning theory for the proposed theoretical model of this study. Framework of this study is built on the tenets of (1) Social Support (2) Entrepreneurial Skills (3) Attitude towards Entrepreneurship (4) Subjective Norms (5) Perceived Behavioural Control (6) Entrepreneurial Intention and (7) Entrepreneurial Behaviour. This study serves as a first step towards exploring the significance of social support and entrepreneurial skills with specific reference to entrepreneurial behaviour. Findings of this study mark the importance of social support and entrepreneurial skills for determining entrepreneurial behaviour. Moreover these findings reveal that social support, entrepreneurial intention and entrepreneurial skills are the main factors which influence entrepreneurial behaviour of individuals. By extending theory of planned behaviour this study has made a sizeable theoretical contribution to the overall body of knowledge. Yet it is pertinent to mention that along with theoretical and methodological contribution, further implications of this study are also devised in a number of allied areas, such as contextual and practical contributions. Findings of this study can serve as torch-bearer for policy makers, academicians and researchers in the field of entrepreneurship. Hence this study covers a considerable potential reap which is possible through social support and entrepreneurial skills development for promoting entrepreneurial behaviour